Analisis Semiotik Simbol Terhadap Bangunan Rumah Adat Suku Simalungun Kabupaten Simalungun - Friokto Winra Purba; Junifer Siregar; Vita Riahni Saragih (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
The problem in this research is analyzing the semiotic symbols in the traditional house buildings of the Simalungun tribe. The type of research used is a qualitative descriptive research method. Qualitative research has a special position that makes the researcher the key instrument. Data collection techniques are the most strategic step in research, because the main aim of research is to obtain data. Data collection techniques in this research are listening techniques and note-taking techniques. Data analysis techniques are the process of systematically searching and compiling the data obtained by organizing the data into categories, breaking it down into units, synthesizing it, arranging it into patterns, selecting the important meanings that will be studied, and making conclusions so that it is easy. understood. The results of research on the traditional house buildings of the Simalungun tribe show that there are many symbols found in the traditional house buildings of the Simalungun tribe.